ARCH MODEL FOR FORECASTING BCA BANK STOCK PRICE VOLATILITY - Surya, Annisa Cahyani; Ariyanto, Adisty Syawalda; Napitupulu, Leonard Andreas; Sihaloho, Ryantoni; S, Mika Alvionita; Muthoharoh, Luluk (VARIANCE: Journal of Statistics and Its Applications, 2025)
This research analyzes the Autoregressive Conditional Heteroskedasticity (ARCH(p) model to predict the BCA Bank share price in the range of January 2013 to November 2023. BCA Bank's share price, as one of the shares traded on the Indonesian Stock Exchange, requires accurate volatility modeling. Researchers use the ARIMA(0,1,2) model as the initial approach, but because of heteroscedasticity, they apply the ARCH(8) model to overcome it. The results show that the ARCH(8) model performs best, with the lowest AIC values for volatility. BCA Bank's daily stock price as of December 1, 2023, showed high volatility, signaling significant risk to investors.